A seven-year longitudinal study of the association between neurocognitive function and basic self-disorders in schizophrenia - Haug, Elisabeth; Øie, Merete G.; Svendsen, Ingrid H.; Møller, Paul; Nelson, Barnaby; Melle, Ingrid (Frontiers in Psychology, 2023)
Basic self-disorders (SDs) and neurocognitive impairments are fundamental trait-like aspects of schizophrenia spectrum disorders. There has been little research on the association between SDs and neurocognitive impairments in schizophrenia, and no longitudinal studies have investigated if they are related. The aim of this study was to investigate the association between SDs and neurocognitive function in a follow-up study of patients with schizophrenia. SDs and neurocognition were examined in 35 patients with schizophrenia during their first treatment and seven years later (mean 7.1, SD 0.42). SDs were examined with the Examination of Anomalous Self-Experience (EASE) instrument. The neurocognitive examination included assessments of psychomotor speed, executive- and memory functions. Poorer executive functions at baseline were significantly associated with more SDs seven years later and smaller reductions in SDs over time. There were no significant associations between other neurocognitive functions and SDs. Executive functions are important for self-regulation, and impairments in these functions in everyday life may have an impact on the development and/or persistence of SDs.